Autoetnografia, infâncias e decolonialidades em (trans)formação - Merlo, Marianna Cardoso Reis (2022)
The main goal of this research is to describe and analyze the researcher education as a young learner English teacher in the light of decolonial and childhood studies. Located within the field of Applied Linguistics, this study adopts autoehnography as the theoretical-metodological perspective, which aims at emphasizing subjectivities and emotions that emerge in the investigation process as well as highlighting the personal experiences that have occurred throughout the researcher’s education process. The data include personal documents and narratives, images, conversations with students and people who have participated in the researcher’s educational process (family, co-workers, classmates, students and school community), as well as audiovisual recording of classes taught by the researcher. This study contributes to broaden knowledge in the teacher education field, particularly when it comes to teaching foreign language to children. This area lacks investigations that articulate childhood philosophy within language studies. It is assumed, in this research, that the teacher education process involves not only the specific time dedicated to initial and continued education, but also entails subjective, emotional, social, environmental and technological dimentions. The study ends up as a defense of a decolonial view to the different possibilities of childhood that are present in the foreign language classroom